Efektivitas Model Pembelajaran Treffinger untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Petris Akbar; Erliany Syaodih; Cucu Lisnawati (Program Studi Pendidikan Ekonomi, FKIP Universitas Langlangbuana, 2015)
The learning model used to measure students' creative thinking is the Treffinger learning model and the usual learning model by teachers in everyday learning. The method in this research using quasi-experimental method and design of the study is a pretest-posttest nonequivalent group design contrtol. In this study, students are divided into two classes: the experimental class treated with Treffinger learning model and grade control using the usual learning model given by the teacher. This research was conducted at SMAN 27 Bandung with sample consist of two classes that class XI IPS 1 and XI IPS 3. The data collection technique using the written test in the form description. The results showed that: (a) From the data processing Treffinger known that the learning model is very effective in improving students' ability to think creatively compared with the usual learning model, (b) preliminary results of data processing is concluded that the ability of the experimental class and control class is not much different from that mean the same and can be said to be homogeneous, (c) based on the hypothesis test obtained results there are significant differences in the improvement of students' creative thinking skills on economic subjects using the Treffinger learning model compared with ordinary learning model, (d) the resulting increase in the gain test experimental class have higher qualifications than the control class that have low qualifications. Therefore, it can be concluded that the classes that get treated Treffinger learning model get increased ability of creative thinking is more significant than the ordinary learning model by the teacher.